Principal leadership, academic supervision, and elementary school teacher performance in a semi-rural school cluster (IAIN Kendari, 2026)
Teacher performance is a key indicator of elementary school quality, particularly in semi-rural contexts where school-based leadership and supervision play a central role in professional development. This study aimed to analyze the statistical effects of principal leadership and academic supervision, both partially and simultaneously, on elementary school teacher performance. A quantitative correlational survey design was employed involving 42 teachers from five elementary schools in the Patimura Cluster, Sapuran District, Wonosobo Regency. Data were collected using three validated Likert-scale questionnaires and analyzed through descriptive statistics, normality and linearity tests, Pearson correlation, and multiple regression. The results showed that principal leadership had a positive and significant relationship with teacher performance, explaining 41% of its variance. Academic supervision also showed a significant positive relationship, explaining 37% of the variance. Simultaneously, both predictors explained 58.7% of teacher performance variance. These findings indicate that teacher performance is strengthened more effectively when principal leadership and academic supervision are integrated as complementary school improvement strategies. Keywords: academic supervision; correlational survey; elementary school; principal leadership; semi-rural education; teacher performance